Cheating under pressure: A self-protection model of workplace cheating behavior - Mitchell, Marie S; Baer, Michael D; Ambrose, Maureen L; Folger, Robert; Palmer, Noel F (Journal of applied psychology, 2018)
[Correction Notice: An Erratum for this article was reported in Vol 103(1) of (see record 2017-44052-001). In the article, the fit statistics in Study 3 were reported in error. The fit of the measurement model is: Χ²(362) = 563.66, p = .001; CFI = .94; SRMR = .05; RMSEA = .04. The fit of the SEM model is: Χ²(362) = 563.66, p = .001; CFI = .94; SRMR = .05; RMSEA = .04.] Workplace cheating behavior is unethical behavior that seeks to create an unfair advantage and enhance benefits for the actor. Although cheating is clearly unwanted behavior within organizations, organizations may unknowingly increase cheating as a byproduct of their pursuit of high performance. We theorize that as organizations place a strong emphasis on high levels of performance, they may also enhance employees' self-interested motives and need for self-protection. We suggest that demands for high performance may elicit performance pressure-the subjective experience that employees must raise their performance efforts or face significant consequences. Employees' perception of the need to raise performance paired with the potential for negative consequences is threatening and heightens self-protection needs. Driven by self-protection, employees experience anger and heightened self-serving cognitions, which motivate cheating behavior. A multistudy approach was used to test our predictions. Study 1 developed and provided validity evidence for a measure of cheating behavior. Studies 2 and 3 tested our predictions in time-separated field studies. Results from Study 2 demonstrated that anger mediates the effects of performance pressure on cheating behavior. Study 3 replicated the Study 2 findings, and extended them to show that self-serving cognitions also mediate the effects of performance pressure on cheating behavior. Implications of our findings for theory and practice are provided. (PsycINFO Database Record